An investigation of the segregation process applied to Western Australian nickel laterites - Grimsey, David Eric (Curtin University, 2015)
An investigation of the segregation process applied to Western Australian nickel laterites, with a particular focus on the relatively unique nontronite zone, was carried out. The main aim was to provide a better understanding of the process through study of its underlying fundamental aspects. The results revealed the key to achieving high recoveries is promoting segregation over the parallel in-situ reduction process, with the mineralogy of the ore playing a key role.